Immunization of mice with Trypanosoma cruzi polyribosomes. - Leon, L L (1980)
Studies were carried out with a polyribosomal fraction isolated from Trypanosoma cruzi Y epimastigotes, with the intention to determine both its immunogenic activity and the degree of protection it could induce against experimental T. cruzi infection. This fraction was assayed in four groups of mice by using different schedules of vaccination and varying the dose, intervals, and route of administration. Seven days after the last dose, the animals were sacrificed for immunological studies or subjected to challenge with T. cruzi trypomastigotes. The results obtained in all schedules showed that our polyribosomal fraction only induced a weak antibody response, but was capable of evoking an expressive cellular response. It was also shown that this fraction has the capacity of inducing a high degree of protection against T. cruzi infection, as determined by the decrease of parasitemia and the prolonged survival time of immunized animals.